Combined Destinies : Whites Sharing Grief about Racism - Horowitz, Pamela, 1946-; Bond, Julian, 1940-2015; Haskell, Caroline T.; Jealous, Ann Todd (Book collections on Project MUSE., 2013)
By beginning a conversation that encourages self-examination and compassion, "Combined Destinies" invites its readers to look at how white Americans have been hurt by the very ideology that their ancestors created. Editors Ann Todd Jealous and Caroline T. Haskell, both experienced psychotherapists skilled at facilitating dialogue about racial issues, are cognizant of the challenges that even the thought of such conversations often presents. Their book is based on the premise that for positive and lasting change to occur, it is necessary to open hearts as well as minds. This courageous anthology posits that unearned privilege has damaged the psyche of white people as well as their capacity to understand racism. Drawing on the intimate stories of diverse contributors, "Combined Destinies" is organized thematically, with individual chapters focusing on topics such as guilt, shame, silence, and resistance. The book includes an extensive reader's guide, posing questions for discussion pertaining to each chapter and offering readers a chance to explore their own experiences.